Pengungkapan Enterprise Risk Management dan Intellectual Capital: Apakah Bermanfaat bagi Perusahaan Real Estate? - Atika Anisaulfitria Putuyana; Dekeng Setyo Budiarto (Universitas Sarjanawiyata Tamansiswa, 2018)
Uncertainty environment, market liberalization, and lower profit margins, firms should make the most efficient use of relevant expenditures related to firm value. This research aims to find out evidences the effect of ERM disclosure, IC disclosure, profitability, leverage ratio on firm value. The sample of the research is 22 property and real estate companies listed in Indonesian Stock Exchange for the period of 2011-2016. The sample collection technique has been carried out by using purposive sampling technique. The data is the secondary data. The data analysis has been carried out by multiple regressions analysis. The result of the analysis show that ERM, IC, has negative influence to the firm value. The profitability and leverage has positive influence to the firm value.Â Keywords: ERM disclosure, IC disclosure, profitability, leverage, firm value